Example #1
0
def test_combsimp():
    k, m, n = symbols('k m n', integer=True)

    assert combsimp(factorial(n)) == factorial(n)
    assert combsimp(binomial(n, k)) == binomial(n, k)

    assert combsimp(factorial(n) / factorial(n - 3)) == n * (-1 + n) * (-2 + n)
    assert combsimp(binomial(n + 1, k + 1) /
                    binomial(n, k)) == (1 + n) / (1 + k)

    assert combsimp(binomial(3*n + 4, n + 1)/binomial(3*n + 1, n)) == \
        Rational(3, 2)*((3*n + 2)*(3*n + 4)/((n + 1)*(2*n + 3)))

    assert combsimp(factorial(n)**2/factorial(n - 3)) == \
        factorial(n)*n*(-1 + n)*(-2 + n)
    assert combsimp(factorial(n)*binomial(n + 1, k + 1)/binomial(n, k)) == \
        factorial(n + 1)/(1 + k)

    assert combsimp(gamma(n + 3)) == factorial(n + 2)

    assert combsimp(factorial(x)) == gamma(x + 1)

    # issue 9699
    assert combsimp((n + 1) * factorial(n)) == factorial(n + 1)
    assert combsimp(factorial(n) / n) == factorial(n - 1)

    # issue 6658
    assert combsimp(binomial(n, n - k)) == binomial(n, k)

    # issue 6341, 7135
    assert combsimp(factorial(n)/(factorial(k)*factorial(n - k))) == \
        binomial(n, k)
    assert combsimp(factorial(k)*factorial(n - k)/factorial(n)) == \
        1/binomial(n, k)
    assert combsimp(factorial(2 * n) / factorial(n)**2) == binomial(2 * n, n)
    assert combsimp(
        factorial(2 * n) * factorial(k) * factorial(n - k) /
        factorial(n)**3) == binomial(2 * n, n) / binomial(n, k)

    assert combsimp(factorial(n * (1 + n) - n**2 - n)) == 1

    assert combsimp(6*FallingFactorial(-4, n)/factorial(n)) == \
        (-1)**n*(n + 1)*(n + 2)*(n + 3)
    assert combsimp(6*FallingFactorial(-4, n - 1)/factorial(n - 1)) == \
        (-1)**(n - 1)*n*(n + 1)*(n + 2)
    assert combsimp(6*FallingFactorial(-4, n - 3)/factorial(n - 3)) == \
        (-1)**(n - 3)*n*(n - 1)*(n - 2)
    assert combsimp(6*FallingFactorial(-4, -n - 1)/factorial(-n - 1)) == \
        -(-1)**(-n - 1)*n*(n - 1)*(n - 2)

    assert combsimp(6*RisingFactorial(4, n)/factorial(n)) == \
        (n + 1)*(n + 2)*(n + 3)
    assert combsimp(6*RisingFactorial(4, n - 1)/factorial(n - 1)) == \
        n*(n + 1)*(n + 2)
    assert combsimp(6*RisingFactorial(4, n - 3)/factorial(n - 3)) == \
        n*(n - 1)*(n - 2)
    assert combsimp(6*RisingFactorial(4, -n - 1)/factorial(-n - 1)) == \
        -n*(n - 1)*(n - 2)
Example #2
0
def test_combsimp():
    from sympy.abc import n, k

    assert combsimp(factorial(n)) == factorial(n)
    assert combsimp(binomial(n, k)) == binomial(n, k)

    assert combsimp(factorial(n) / factorial(n - 3)) == n * (-1 + n) * (-2 + n)
    assert combsimp(binomial(n + 1, k + 1) /
                    binomial(n, k)) == (1 + n) / (1 + k)

    assert combsimp(binomial(3*n + 4, n + 1)/binomial(3*n + 1, n)) == \
        S(3)/2*((3*n + 2)*(3*n + 4)/((n + 1)*(2*n + 3)))

    assert combsimp(factorial(n)**2/factorial(n - 3)) == \
        factorial(n)*n*(-1 + n)*(-2 + n)
    assert combsimp(factorial(n)*binomial(n + 1, k + 1)/binomial(n, k)) == \
        factorial(n + 1)/(1 + k)

    assert combsimp(binomial(n - 1, k)) == -((-n + k) * binomial(n, k)) / n

    assert combsimp(binomial(n + 2, k + S(1) / 2)) == 4 * (
        (n + 1) * (n + 2) * binomial(n, k + S(1) / 2)) / ((2 * k - 2 * n - 1) *
                                                          (2 * k - 2 * n - 3))
    assert combsimp(binomial(n + 2, k + 2.0)) == \
        Mul(-2.0, 0.5*n + 1.0, binomial(n + 1.0, k + 2.0),
        evaluate = False)/(k - n)

    # coverage tests
    assert combsimp(factorial(n * (1 + n) - n**2 - n)) == 1
    assert combsimp(binomial(n + k - 2, n)) == \
        k*(k - 1)*binomial(n + k, n)/((n + k)*(n + k - 1))
    i = Symbol('i', integer=True)
    e = gamma(i + 3)
    assert combsimp(e) == e
    e = gamma(exp(i))
    assert combsimp(e) == e
    e = gamma(n + S(1) / 3) * gamma(n + S(2) / 3)
    assert combsimp(e) == e
    assert combsimp(gamma(4*n + S(1)/2)/gamma(2*n - S(3)/4)) == \
        2**(4*n - S(5)/2)*(8*n - 3)*gamma(2*n + S(3)/4)/sqrt(pi)

    assert combsimp(6*FallingFactorial(-4, n)/factorial(n)) == \
        (-1)**n*(n + 1)*(n + 2)*(n + 3)
    assert combsimp(6*FallingFactorial(-4, n - 1)/factorial(n - 1)) == \
        (-1)**(n - 1)*n*(n + 1)*(n + 2)
    assert combsimp(6*FallingFactorial(-4, n - 3)/factorial(n - 3)) == \
        (-1)**(n - 3)*n*(n - 1)*(n - 2)
    assert combsimp(6*FallingFactorial(-4, -n - 1)/factorial(-n - 1)) == \
        -(-1)**(-n - 1)*n*(n - 1)*(n - 2)

    assert combsimp(6*RisingFactorial(4, n)/factorial(n)) == \
        (n + 1)*(n + 2)*(n + 3)
    assert combsimp(6*RisingFactorial(4, n - 1)/factorial(n - 1)) == \
        n*(n + 1)*(n + 2)
    assert combsimp(6*RisingFactorial(4, n - 3)/factorial(n - 3)) == \
        n*(n - 1)*(n - 2)
    assert combsimp(6*RisingFactorial(4, -n - 1)/factorial(-n - 1)) == \
        -n*(n - 1)*(n - 2)
Example #3
0
def test_latex_functions():
    assert latex(exp(x)) == "e^{x}"
    assert latex(exp(1) + exp(2)) == "e + e^{2}"

    f = Function('f')
    assert latex(f(x)) == '\\operatorname{f}{\\left (x \\right )}'

    beta = Function('beta')

    assert latex(beta(x)) == r"\beta{\left (x \right )}"
    assert latex(sin(x)) == r"\sin{\left (x \right )}"
    assert latex(sin(x), fold_func_brackets=True) == r"\sin {x}"
    assert latex(sin(2*x**2), fold_func_brackets=True) == \
    r"\sin {2 x^{2}}"
    assert latex(sin(x**2), fold_func_brackets=True) == \
    r"\sin {x^{2}}"

    assert latex(asin(x)**2) == r"\operatorname{asin}^{2}{\left (x \right )}"
    assert latex(asin(x)**2,inv_trig_style="full") == \
        r"\arcsin^{2}{\left (x \right )}"
    assert latex(asin(x)**2,inv_trig_style="power") == \
        r"\sin^{-1}{\left (x \right )}^{2}"
    assert latex(asin(x**2),inv_trig_style="power",fold_func_brackets=True) == \
        r"\sin^{-1} {x^{2}}"

    assert latex(factorial(k)) == r"k!"
    assert latex(factorial(-k)) == r"\left(- k\right)!"

    assert latex(factorial2(k)) == r"k!!"
    assert latex(factorial2(-k)) == r"\left(- k\right)!!"

    assert latex(binomial(2, k)) == r"{\binom{2}{k}}"

    assert latex(FallingFactorial(3,
                                  k)) == r"{\left(3\right)}_{\left(k\right)}"
    assert latex(RisingFactorial(3, k)) == r"{\left(3\right)}^{\left(k\right)}"

    assert latex(floor(x)) == r"\lfloor{x}\rfloor"
    assert latex(ceiling(x)) == r"\lceil{x}\rceil"
    assert latex(Abs(x)) == r"\lvert{x}\rvert"
    assert latex(re(x)) == r"\Re{x}"
    assert latex(re(x + y)) == r"\Re {\left (x + y \right )}"
    assert latex(im(x)) == r"\Im{x}"
    assert latex(conjugate(x)) == r"\overline{x}"
    assert latex(gamma(x)) == r"\Gamma\left(x\right)"
    assert latex(Order(x)) == r"\mathcal{O}\left(x\right)"
    assert latex(lowergamma(x, y)) == r'\gamma\left(x, y\right)'
    assert latex(uppergamma(x, y)) == r'\Gamma\left(x, y\right)'

    assert latex(cot(x)) == r'\cot{\left (x \right )}'
    assert latex(coth(x)) == r'\coth{\left (x \right )}'
    assert latex(re(x)) == r'\Re{x}'
    assert latex(im(x)) == r'\Im{x}'
    assert latex(root(x, y)) == r'x^{\frac{1}{y}}'
    assert latex(arg(x)) == r'\arg{\left (x \right )}'
    assert latex(zeta(x)) == r'\zeta{\left (x \right )}'
Example #4
0
def test_factorial_moment():
    X = Poisson('X', 2)
    Y = Binomial('Y', 2, S.Half)
    Z = Hypergeometric('Z', 4, 2, 2)
    assert factorial_moment(X, 2) == 4
    assert factorial_moment(Y, 2) == S.Half
    assert factorial_moment(Z, 2) == Rational(1, 3)

    x, y, z, l = symbols('x y z l')
    Y = Binomial('Y', 2, y)
    Z = Hypergeometric('Z', 10, 2, 3)
    assert factorial_moment(Y, l) == y**2*FallingFactorial(
        2, l) + 2*y*(1 - y)*FallingFactorial(1, l) + (1 - y)**2*\
            FallingFactorial(0, l)
    assert factorial_moment(Z, l) == 7*FallingFactorial(0, l)/\
        15 + 7*FallingFactorial(1, l)/15 + FallingFactorial(2, l)/15
Example #5
0
def factorial_moment(X, n, condition=None, **kwargs):
    """
    The factorial moment is a mathematical quantity defined as the expectation
    or average of the falling factorial of a random variable.

    .. math::
        factorial-moment(X, n) = E(X(X - 1)(X - 2)...(X - n + 1))

    Parameters
    ==========

    n: A natural number, n-th factorial moment.

    condition : Expr containing RandomSymbols
            A conditional expression.

    Examples
    ========

    >>> from sympy.stats import factorial_moment, Poisson, Binomial
    >>> from sympy import Symbol, S
    >>> lamda = Symbol('lamda')
    >>> X = Poisson('X', lamda)
    >>> factorial_moment(X, 2)
    lamda**2
    >>> Y = Binomial('Y', 2, S.Half)
    >>> factorial_moment(Y, 2)
    1/2
    >>> factorial_moment(Y, 2, Y > 1) # find factorial moment for Y > 1
    2

    References
    ==========

    .. [1] https://en.wikipedia.org/wiki/Factorial_moment
    .. [2] http://mathworld.wolfram.com/FactorialMoment.html
    """
    return expectation(FallingFactorial(X, n), condition=condition, **kwargs)
Example #6
0
def test_factorial_moment():
    X = Poisson("X", 2)
    Y = Binomial("Y", 2, S.Half)
    Z = Hypergeometric("Z", 4, 2, 2)
    assert factorial_moment(X, 2) == 4
    assert factorial_moment(Y, 2) == S.Half
    assert factorial_moment(Z, 2) == Rational(1, 3)

    x, y, z, l = symbols("x y z l")
    Y = Binomial("Y", 2, y)
    Z = Hypergeometric("Z", 10, 2, 3)
    assert factorial_moment(Y, l) == y ** 2 * FallingFactorial(2, l) + 2 * y * (
        1 - y
    ) * FallingFactorial(1, l) + (1 - y) ** 2 * FallingFactorial(0, l)
    assert (
        factorial_moment(Z, l)
        == 7 * FallingFactorial(0, l) / 15
        + 7 * FallingFactorial(1, l) / 15
        + FallingFactorial(2, l) / 15
    )
Example #7
0
def test_latex_functions():
    assert latex(exp(x)) == "e^{x}"
    assert latex(exp(1) + exp(2)) == "e + e^{2}"

    f = Function('f')
    assert latex(f(x)) == '\\operatorname{f}{\\left (x \\right )}'

    beta = Function('beta')

    assert latex(beta(x)) == r"\beta{\left (x \right )}"
    assert latex(sin(x)) == r"\sin{\left (x \right )}"
    assert latex(sin(x), fold_func_brackets=True) == r"\sin {x}"
    assert latex(sin(2*x**2), fold_func_brackets=True) == \
        r"\sin {2 x^{2}}"
    assert latex(sin(x**2), fold_func_brackets=True) == \
        r"\sin {x^{2}}"

    assert latex(asin(x)**2) == r"\operatorname{asin}^{2}{\left (x \right )}"
    assert latex(asin(x)**2, inv_trig_style="full") == \
        r"\arcsin^{2}{\left (x \right )}"
    assert latex(asin(x)**2, inv_trig_style="power") == \
        r"\sin^{-1}{\left (x \right )}^{2}"
    assert latex(asin(x**2), inv_trig_style="power",
                 fold_func_brackets=True) == \
        r"\sin^{-1} {x^{2}}"

    assert latex(factorial(k)) == r"k!"
    assert latex(factorial(-k)) == r"\left(- k\right)!"

    assert latex(subfactorial(k)) == r"!k"
    assert latex(subfactorial(-k)) == r"!\left(- k\right)"

    assert latex(factorial2(k)) == r"k!!"
    assert latex(factorial2(-k)) == r"\left(- k\right)!!"

    assert latex(binomial(2, k)) == r"{\binom{2}{k}}"

    assert latex(FallingFactorial(3,
                                  k)) == r"{\left(3\right)}_{\left(k\right)}"
    assert latex(RisingFactorial(3, k)) == r"{\left(3\right)}^{\left(k\right)}"

    assert latex(floor(x)) == r"\lfloor{x}\rfloor"
    assert latex(ceiling(x)) == r"\lceil{x}\rceil"
    assert latex(Min(x, 2, x**3)) == r"\min\left(2, x, x^{3}\right)"
    assert latex(Min(x, y)**2) == r"\min\left(x, y\right)^{2}"
    assert latex(Max(x, 2, x**3)) == r"\max\left(2, x, x^{3}\right)"
    assert latex(Max(x, y)**2) == r"\max\left(x, y\right)^{2}"
    assert latex(Abs(x)) == r"\lvert{x}\rvert"
    assert latex(re(x)) == r"\Re{x}"
    assert latex(re(x + y)) == r"\Re{x} + \Re{y}"
    assert latex(im(x)) == r"\Im{x}"
    assert latex(conjugate(x)) == r"\overline{x}"
    assert latex(gamma(x)) == r"\Gamma\left(x\right)"
    assert latex(Order(x)) == r"\mathcal{O}\left(x\right)"
    assert latex(lowergamma(x, y)) == r'\gamma\left(x, y\right)'
    assert latex(uppergamma(x, y)) == r'\Gamma\left(x, y\right)'

    assert latex(cot(x)) == r'\cot{\left (x \right )}'
    assert latex(coth(x)) == r'\coth{\left (x \right )}'
    assert latex(re(x)) == r'\Re{x}'
    assert latex(im(x)) == r'\Im{x}'
    assert latex(root(x, y)) == r'x^{\frac{1}{y}}'
    assert latex(arg(x)) == r'\arg{\left (x \right )}'
    assert latex(zeta(x)) == r'\zeta\left(x\right)'

    assert latex(zeta(x)) == r"\zeta\left(x\right)"
    assert latex(zeta(x)**2) == r"\zeta^{2}\left(x\right)"
    assert latex(zeta(x, y)) == r"\zeta\left(x, y\right)"
    assert latex(zeta(x, y)**2) == r"\zeta^{2}\left(x, y\right)"
    assert latex(dirichlet_eta(x)) == r"\eta\left(x\right)"
    assert latex(dirichlet_eta(x)**2) == r"\eta^{2}\left(x\right)"
    assert latex(polylog(x, y)) == r"\operatorname{Li}_{x}\left(y\right)"
    assert latex(polylog(x,
                         y)**2) == r"\operatorname{Li}_{x}^{2}\left(y\right)"
    assert latex(lerchphi(x, y, n)) == r"\Phi\left(x, y, n\right)"
    assert latex(lerchphi(x, y, n)**2) == r"\Phi^{2}\left(x, y, n\right)"

    assert latex(Ei(x)) == r'\operatorname{Ei}{\left (x \right )}'
    assert latex(Ei(x)**2) == r'\operatorname{Ei}^{2}{\left (x \right )}'
    assert latex(expint(x, y)**2) == r'\operatorname{E}_{x}^{2}\left(y\right)'
    assert latex(Shi(x)**2) == r'\operatorname{Shi}^{2}{\left (x \right )}'
    assert latex(Si(x)**2) == r'\operatorname{Si}^{2}{\left (x \right )}'
    assert latex(Ci(x)**2) == r'\operatorname{Ci}^{2}{\left (x \right )}'
    assert latex(Chi(x)**2) == r'\operatorname{Chi}^{2}{\left (x \right )}'

    assert latex(jacobi(n, a, b,
                        x)) == r'P_{n}^{\left(a,b\right)}\left(x\right)'
    assert latex(jacobi(
        n, a, b,
        x)**2) == r'\left(P_{n}^{\left(a,b\right)}\left(x\right)\right)^{2}'
    assert latex(gegenbauer(n, a,
                            x)) == r'C_{n}^{\left(a\right)}\left(x\right)'
    assert latex(gegenbauer(
        n, a,
        x)**2) == r'\left(C_{n}^{\left(a\right)}\left(x\right)\right)^{2}'
    assert latex(chebyshevt(n, x)) == r'T_{n}\left(x\right)'
    assert latex(chebyshevt(n,
                            x)**2) == r'\left(T_{n}\left(x\right)\right)^{2}'
    assert latex(chebyshevu(n, x)) == r'U_{n}\left(x\right)'
    assert latex(chebyshevu(n,
                            x)**2) == r'\left(U_{n}\left(x\right)\right)^{2}'
    assert latex(legendre(n, x)) == r'P_{n}\left(x\right)'
    assert latex(legendre(n, x)**2) == r'\left(P_{n}\left(x\right)\right)^{2}'
    assert latex(assoc_legendre(n, a,
                                x)) == r'P_{n}^{\left(a\right)}\left(x\right)'
    assert latex(assoc_legendre(
        n, a,
        x)**2) == r'\left(P_{n}^{\left(a\right)}\left(x\right)\right)^{2}'
    assert latex(laguerre(n, x)) == r'L_{n}\left(x\right)'
    assert latex(laguerre(n, x)**2) == r'\left(L_{n}\left(x\right)\right)^{2}'
    assert latex(assoc_laguerre(n, a,
                                x)) == r'L_{n}^{\left(a\right)}\left(x\right)'
    assert latex(assoc_laguerre(
        n, a,
        x)**2) == r'\left(L_{n}^{\left(a\right)}\left(x\right)\right)^{2}'
    assert latex(hermite(n, x)) == r'H_{n}\left(x\right)'
    assert latex(hermite(n, x)**2) == r'\left(H_{n}\left(x\right)\right)^{2}'

    # Test latex printing of function names with "_"
    assert latex(
        polar_lift(0)) == r"\operatorname{polar\_lift}{\left (0 \right )}"
    assert latex(polar_lift(0)**
                 3) == r"\operatorname{polar\_lift}^{3}{\left (0 \right )}"
Example #8
0
def test_latex_functions():
    assert latex(exp(x)) == "e^{x}"
    assert latex(exp(1) + exp(2)) == "e + e^{2}"

    f = Function('f')
    assert latex(f(x)) == r'f{\left (x \right )}'
    assert latex(f) == r'f'

    g = Function('g')
    assert latex(g(x, y)) == r'g{\left (x,y \right )}'
    assert latex(g) == r'g'

    h = Function('h')
    assert latex(h(x, y, z)) == r'h{\left (x,y,z \right )}'
    assert latex(h) == r'h'

    Li = Function('Li')
    assert latex(Li) == r'\operatorname{Li}'
    assert latex(Li(x)) == r'\operatorname{Li}{\left (x \right )}'

    beta = Function('beta')

    # not to be confused with the beta function
    assert latex(beta(x)) == r"\beta{\left (x \right )}"
    assert latex(beta) == r"\beta"

    assert latex(sin(x)) == r"\sin{\left (x \right )}"
    assert latex(sin(x), fold_func_brackets=True) == r"\sin {x}"
    assert latex(sin(2*x**2), fold_func_brackets=True) == \
        r"\sin {2 x^{2}}"
    assert latex(sin(x**2), fold_func_brackets=True) == \
        r"\sin {x^{2}}"

    assert latex(asin(x)**2) == r"\operatorname{asin}^{2}{\left (x \right )}"
    assert latex(asin(x)**2, inv_trig_style="full") == \
        r"\arcsin^{2}{\left (x \right )}"
    assert latex(asin(x)**2, inv_trig_style="power") == \
        r"\sin^{-1}{\left (x \right )}^{2}"
    assert latex(asin(x**2), inv_trig_style="power",
                 fold_func_brackets=True) == \
        r"\sin^{-1} {x^{2}}"

    assert latex(factorial(k)) == r"k!"
    assert latex(factorial(-k)) == r"\left(- k\right)!"

    assert latex(subfactorial(k)) == r"!k"
    assert latex(subfactorial(-k)) == r"!\left(- k\right)"

    assert latex(factorial2(k)) == r"k!!"
    assert latex(factorial2(-k)) == r"\left(- k\right)!!"

    assert latex(binomial(2, k)) == r"{\binom{2}{k}}"

    assert latex(FallingFactorial(3,
                                  k)) == r"{\left(3\right)}_{\left(k\right)}"
    assert latex(RisingFactorial(3, k)) == r"{\left(3\right)}^{\left(k\right)}"

    assert latex(floor(x)) == r"\lfloor{x}\rfloor"
    assert latex(ceiling(x)) == r"\lceil{x}\rceil"
    assert latex(Min(x, 2, x**3)) == r"\min\left(2, x, x^{3}\right)"
    assert latex(Min(x, y)**2) == r"\min\left(x, y\right)^{2}"
    assert latex(Max(x, 2, x**3)) == r"\max\left(2, x, x^{3}\right)"
    assert latex(Max(x, y)**2) == r"\max\left(x, y\right)^{2}"
    assert latex(Abs(x)) == r"\left\lvert{x}\right\rvert"
    assert latex(re(x)) == r"\Re{x}"
    assert latex(re(x + y)) == r"\Re{x} + \Re{y}"
    assert latex(im(x)) == r"\Im{x}"
    assert latex(conjugate(x)) == r"\overline{x}"
    assert latex(gamma(x)) == r"\Gamma{\left(x \right)}"
    w = Wild('w')
    assert latex(gamma(w)) == r"\Gamma{\left(w \right)}"
    assert latex(Order(x)) == r"\mathcal{O}\left(x\right)"
    assert latex(Order(x, x)) == r"\mathcal{O}\left(x\right)"
    assert latex(Order(x, x, 0)) == r"\mathcal{O}\left(x\right)"
    assert latex(Order(x, x,
                       oo)) == r"\mathcal{O}\left(x; x\rightarrow\infty\right)"
    assert latex(
        Order(x, x, y)
    ) == r"\mathcal{O}\left(x; \begin{pmatrix}x, & y\end{pmatrix}\rightarrow0\right)"
    assert latex(
        Order(x, x, y, 0)
    ) == r"\mathcal{O}\left(x; \begin{pmatrix}x, & y\end{pmatrix}\rightarrow0\right)"
    assert latex(
        Order(x, x, y, oo)
    ) == r"\mathcal{O}\left(x; \begin{pmatrix}x, & y\end{pmatrix}\rightarrow\infty\right)"
    assert latex(lowergamma(x, y)) == r'\gamma\left(x, y\right)'
    assert latex(uppergamma(x, y)) == r'\Gamma\left(x, y\right)'

    assert latex(cot(x)) == r'\cot{\left (x \right )}'
    assert latex(coth(x)) == r'\coth{\left (x \right )}'
    assert latex(re(x)) == r'\Re{x}'
    assert latex(im(x)) == r'\Im{x}'
    assert latex(root(x, y)) == r'x^{\frac{1}{y}}'
    assert latex(arg(x)) == r'\arg{\left (x \right )}'
    assert latex(zeta(x)) == r'\zeta\left(x\right)'

    assert latex(zeta(x)) == r"\zeta\left(x\right)"
    assert latex(zeta(x)**2) == r"\zeta^{2}\left(x\right)"
    assert latex(zeta(x, y)) == r"\zeta\left(x, y\right)"
    assert latex(zeta(x, y)**2) == r"\zeta^{2}\left(x, y\right)"
    assert latex(dirichlet_eta(x)) == r"\eta\left(x\right)"
    assert latex(dirichlet_eta(x)**2) == r"\eta^{2}\left(x\right)"
    assert latex(polylog(x, y)) == r"\operatorname{Li}_{x}\left(y\right)"
    assert latex(polylog(x,
                         y)**2) == r"\operatorname{Li}_{x}^{2}\left(y\right)"
    assert latex(lerchphi(x, y, n)) == r"\Phi\left(x, y, n\right)"
    assert latex(lerchphi(x, y, n)**2) == r"\Phi^{2}\left(x, y, n\right)"

    assert latex(elliptic_k(z)) == r"K\left(z\right)"
    assert latex(elliptic_k(z)**2) == r"K^{2}\left(z\right)"
    assert latex(elliptic_f(x, y)) == r"F\left(x\middle| y\right)"
    assert latex(elliptic_f(x, y)**2) == r"F^{2}\left(x\middle| y\right)"
    assert latex(elliptic_e(x, y)) == r"E\left(x\middle| y\right)"
    assert latex(elliptic_e(x, y)**2) == r"E^{2}\left(x\middle| y\right)"
    assert latex(elliptic_e(z)) == r"E\left(z\right)"
    assert latex(elliptic_e(z)**2) == r"E^{2}\left(z\right)"
    assert latex(elliptic_pi(x, y, z)) == r"\Pi\left(x; y\middle| z\right)"
    assert latex(elliptic_pi(x, y, z)**2) == \
        r"\Pi^{2}\left(x; y\middle| z\right)"
    assert latex(elliptic_pi(x, y)) == r"\Pi\left(x\middle| y\right)"
    assert latex(elliptic_pi(x, y)**2) == r"\Pi^{2}\left(x\middle| y\right)"

    assert latex(Ei(x)) == r'\operatorname{Ei}{\left (x \right )}'
    assert latex(Ei(x)**2) == r'\operatorname{Ei}^{2}{\left (x \right )}'
    assert latex(expint(x, y)**2) == r'\operatorname{E}_{x}^{2}\left(y\right)'
    assert latex(Shi(x)**2) == r'\operatorname{Shi}^{2}{\left (x \right )}'
    assert latex(Si(x)**2) == r'\operatorname{Si}^{2}{\left (x \right )}'
    assert latex(Ci(x)**2) == r'\operatorname{Ci}^{2}{\left (x \right )}'
    assert latex(Chi(x)**2) == r'\operatorname{Chi}^{2}{\left (x \right )}'
    assert latex(Chi(x)) == r'\operatorname{Chi}{\left (x \right )}'

    assert latex(jacobi(n, a, b,
                        x)) == r'P_{n}^{\left(a,b\right)}\left(x\right)'
    assert latex(jacobi(
        n, a, b,
        x)**2) == r'\left(P_{n}^{\left(a,b\right)}\left(x\right)\right)^{2}'
    assert latex(gegenbauer(n, a,
                            x)) == r'C_{n}^{\left(a\right)}\left(x\right)'
    assert latex(gegenbauer(
        n, a,
        x)**2) == r'\left(C_{n}^{\left(a\right)}\left(x\right)\right)^{2}'
    assert latex(chebyshevt(n, x)) == r'T_{n}\left(x\right)'
    assert latex(chebyshevt(n,
                            x)**2) == r'\left(T_{n}\left(x\right)\right)^{2}'
    assert latex(chebyshevu(n, x)) == r'U_{n}\left(x\right)'
    assert latex(chebyshevu(n,
                            x)**2) == r'\left(U_{n}\left(x\right)\right)^{2}'
    assert latex(legendre(n, x)) == r'P_{n}\left(x\right)'
    assert latex(legendre(n, x)**2) == r'\left(P_{n}\left(x\right)\right)^{2}'
    assert latex(assoc_legendre(n, a,
                                x)) == r'P_{n}^{\left(a\right)}\left(x\right)'
    assert latex(assoc_legendre(
        n, a,
        x)**2) == r'\left(P_{n}^{\left(a\right)}\left(x\right)\right)^{2}'
    assert latex(laguerre(n, x)) == r'L_{n}\left(x\right)'
    assert latex(laguerre(n, x)**2) == r'\left(L_{n}\left(x\right)\right)^{2}'
    assert latex(assoc_laguerre(n, a,
                                x)) == r'L_{n}^{\left(a\right)}\left(x\right)'
    assert latex(assoc_laguerre(
        n, a,
        x)**2) == r'\left(L_{n}^{\left(a\right)}\left(x\right)\right)^{2}'
    assert latex(hermite(n, x)) == r'H_{n}\left(x\right)'
    assert latex(hermite(n, x)**2) == r'\left(H_{n}\left(x\right)\right)^{2}'

    theta = Symbol("theta", real=True)
    phi = Symbol("phi", real=True)
    assert latex(Ynm(n, m, theta, phi)) == r'Y_{n}^{m}\left(\theta,\phi\right)'
    assert latex(
        Ynm(n, m, theta,
            phi)**3) == r'\left(Y_{n}^{m}\left(\theta,\phi\right)\right)^{3}'
    assert latex(Znm(n, m, theta, phi)) == r'Z_{n}^{m}\left(\theta,\phi\right)'
    assert latex(
        Znm(n, m, theta,
            phi)**3) == r'\left(Z_{n}^{m}\left(\theta,\phi\right)\right)^{3}'

    # Test latex printing of function names with "_"
    assert latex(
        polar_lift(0)) == r"\operatorname{polar\_lift}{\left (0 \right )}"
    assert latex(polar_lift(0)**
                 3) == r"\operatorname{polar\_lift}^{3}{\left (0 \right )}"

    assert latex(totient(n)) == r'\phi\left( n \right)'

    # some unknown function name should get rendered with \operatorname
    fjlkd = Function('fjlkd')
    assert latex(fjlkd(x)) == r'\operatorname{fjlkd}{\left (x \right )}'
    # even when it is referred to without an argument
    assert latex(fjlkd) == r'\operatorname{fjlkd}'